Analytical method for the prediction of natural frequencies of switched reluctance motor based on electromechanical analogy method. Issue 1 (2nd January 2018) - Tan, Chao; Wang, Honghua; Chen, Ling
Abstract : Purpose: An improved analytical method for calculating the natural frequencies of a switched reluctance motor (SRM) stator is proposed in this paper. The method is different from traditional analytical methods, which only consider the influence of mass of the stator poles and windings on the natural frequencies of the SRM stator. This paper aims to consider the influence of stiffness and mass of the stator poles and windings simultaneously and reasonably. Design/methodology/approach: An innovated analytical method based on the electromechanical analogy method is presented. In the proposed analytical formulae for calculating the natural frequencies, the influence of the windings on natural frequencies is considered by using the springs to simulate the flexible connection between the stator core and windings, and the stator poles are treated as both additional mass and additional equivalent stiffness. Both three-dimensional (3D) finite-element analysis (FEA) and experimental modal analysis results validate the improved method. Findings: The influence of the mass and stiffness of stator winding is considered by using the springs to simulate the flexible connection between the stator core and windings, and the stator poles are treated as both additional mass and additional equivalent stiffness. The traditional analytical method only considers the influence of mass. Therefore, the calculation results are comparatively lower than 3D FEA results and may lead to a large error. The 3D FEA and experimental modal analysis confirm that the proposed method has good precision for low-order natural frequency calculation of SRMs. Originality/value: An improved analytical method for calculating the natural frequencies of an SRM stator is proposed. Unlike the traditional analytical method, the proposed method can consider the influence of stiffness and mass of the stator poles and windings. This method is valuable for designers to predict the natural frequencies accurately.